2015
DOI: 10.1007/s10047-015-0882-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bloodstream infections on catheter colonization during extracorporeal membrane oxygenation

Abstract: There are concerns about secondary extracorporeal membrane oxygenation (ECMO) catheter infections in bacteremic patients. We investigated the association between blood stream infection (BSI) and ECMO catheter colonization. From January 2012 to August 2014, 47 adults who received ECMO support were enrolled. The ECMO catheter tip was cultured at the end of the ECMO procedure. The enrolled patients were classified into two groups according to the presence of BSI during ECMO support and analyzed with respect to EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…These factors are thought to predispose them to fungal colonization and infection. Recently reported data suggest that up to 15% of all bloodstream infections while on ECMO are of fungal origin [ 16 ]. A 6.4% prevalence of CBSI in an Australian center has been reported [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors are thought to predispose them to fungal colonization and infection. Recently reported data suggest that up to 15% of all bloodstream infections while on ECMO are of fungal origin [ 16 ]. A 6.4% prevalence of CBSI in an Australian center has been reported [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannulas are maintained for several days to weeks depending on the patient's condition, and exchanging cannulas is almost impossible. Blood stream infections (BSI) are signi cant complications of ECMO, and they are associated with mortality, morbidity, and increased healthcare costs in ECMO patients [5]. Bacteremia during ECMO has been associated with catheter colonization, and in a previous study we found bio lm related infections in ECMO catheters.…”
Section: Introductionmentioning
confidence: 97%
“…Depending on the patient's condition, ECMO treatment may last several days or longer, but its presence is a major risk factor for blood stream infection (BSI). In previous studies, it was found that 19-32% of inserted ECMO catheters were colonized with potentially pathogenic bacteria at the point of removal and that about 10% were associated with ECMO device infection [1,2]. While BSI occurrence during ECMO is a serious complication associated with significant morbidity and mortality, its prevalence has been reported to be as much as 3-18% in adults [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely to only increase the risk of resistant strain development and can potentially lead to yeast overgrowth [4]. Given that the predominant organisms colonizing ECMO catheters were found to be gram-positive cocci and Candida species [1,2], it seems likely that skin bacteria traverse the insertion site onto the catheter, where they colonize the circuit and act as a focus for BSI. Furthermore, manipulation of hub for the use of renal replacement therapy (RRT) during ECMO, or for oxygenator function test, and exchange of oxygenator or catheters potentially pose a risk of BSI.…”
Section: Introductionmentioning
confidence: 99%